Newspaper stands as centers of social consciousness in Nigeria (2013)
The existing interaction between newspaper stands and Nigerian readers transcends market exchange. It is rather a place for engendering social consciousness among a people, desirous of being abreast of up-to-date information, but lacking requisite finance. Thus, a practice which evolved out of peoples’ financial incapability has become a catalyst for the congregation of individuals at newspaper stands to access news at minimal cost, for social interaction and possible social consciousness. This depicts a public sphere where people have “shared interest”. Thus, the newspaper stand presents as public sphere where shared public interest reported in newspapers ignites deliberative discourses which hugely impacts social consciousness among discussants and listening by-standers.